KARAKTERISTIK FISIKOKIMIA SNACK BARS TEPUNG AMPAS KELAPA (Cocos nucifera L.) DAN TEPUNG UBI JALAR KUNING (Ipomea batatas L.) - Pandiangan, Cenny Sulastri Br.; Langi, Tineke M.; Mandey, Lucia C. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2021)
ABSTRACTModern community life makes the need for fast food increases. One of the fast foods that is often consumed is cereal and beans. This research was conducted to produce snack bars that are healthy and rich in fiber. This study uses a completely randomized design (CRD) research method with the treatment of coconut pulp and yellow sweet potato flour, each treatment is carried out with 3 replications. The parameters tested were chemical properties (water content, ash content, protein content, fat content, carbohydrate, crude fiber, and antioxidant activity), physical properties (hardness test), and sensory properties (color, taste, scent, and texture).Based on the organoleptic test results of snack bars the panelists preferred were treatment C (50% coconut pulp flour : 50% yellow sweet potato flour) with moisture content of 28.28%, ash content of 1.60%, protein content of 7.74%, content of fat 14.27%, carbohydrates 48.11%, crude fiber 12.51%, antioxidant activity 49.64 ppm, and in terms of physical properties the hardness level is 80.55 mm/g/sec. Keywords : Snack Bars , Coconut Pulp Flour, Yellow Yam Flour ABSTRAKKehidupan masyarakat yang modern membuat kebutuhan makanan siap saji semakin meningkat. Salah satu makanan siap saji yang sering dikonsumsi adalah sereal dan kacang-kacangan. Penelitian ini dilakukan untuk menghasilkan produk snack bars yang sehat dan kaya akan serat. Penelitian ini menggunakan metode penelitian Rancangan Acak Lengkap (RAL) dengan perlakuan tepung ampas kelapa dan tepung ubi jalar kuning masing-masing perlakuan dilakukan dengan 3 kali pengulangan. Parameter yang diuji adalah sifat kimia (kadar air, kadar abu, kadar protein, kadar lemak, karbohidrat, serat kasar, dan aktivitas antioksidan), sifat fisik (uji tingkat kekerasan), dan sifat sensoris (warna, rasa, aroma, dan tekstur).Berdasarkan hasil uji organoleptik snack bars yang paling disukai panelis adalah perlakuan C (50% tepung ampas kelapa : 50% tepung ubi jalar kuning) dimana kadar air 28,28%, kadar abu 1,60%, protein 7,74%, lemak 14,27%, karbohidrat 48,11%, serat kasar 12,51%, aktivitas antioksidan 49,64 ppm, dan sifat fisik tingkat kekerasan 80,55 mm/g/det.Kata kunci: Snack bars, Tepung Ampas Kelapa, Tepung Ubi Jalar Kuning